Pengembangan Media Pembelajaran Low Carbon Poly Berbasis Science Edutainment Pada Tema Jejak Si Karbon - Siti Aulia Nabila; Suroso Mukti Leksono; Vica Dian Aprelia Resti (PendIPA Journal of Science Education, 2022)
Science education-based local media on the carbon footprint subject was developed in order to demonstrate the creation and description of the learning media that have been prepared. There are three stages in the R&D process: define, design, and development. The R&D approach is based on Thiagarajan et al. (1974)'s development model. In-depth interviews and expert-led validity tests are undertaken using a variety of instrument. Descriptive quantitative and qualitative analyses were performed on the data. The results of this study obtained a score of 93.8% (very feasible) in terms of feasibility, 98.4% (very feasible) in the presentation aspect, 94.3% (very feasible) in the graphic aspect, and 99.7% (very feasible). in the language aspect. So that when viewed as a whole, the aspect obtained a value of 96.5% with very feasible criteria.